Collaborative Study for Analysis of Subvisible Particles Using Flow Imaging and Light Obscuration: Experiences in Japanese Biopharmaceutical Consortium - Kiyoshi, Masato; Shibata, Hiroko; Harazono, Akira; Torisu, Tetsuo; Maruno, Takahiro; Akimaru, Michiko; Asano, Yuuka; Hirokawa, Mai; Ikemoto, Keisuke; Itakura, Yukari; Iwura, Takafumi; Kikitsu, Aya; et al. (Journal of pharmaceutical sciences, 2019)
The evaluation of subvisible particles, including protein aggregates, in therapeutic protein products has been of great interest for both pharmaceutical manufacturers and regulatory agencies. To date, the flow imaging (FI) method has emerged as a powerful tool instead of light obscuration (LO) due to the fact that (1) protein aggregates contain highly transparent particles and thereby escape detection by LO and (2) FI provides detailed morphological characteristics of subvisible particles. However, the FI method has not yet been standardized nor listed in any compendium. In an attempt to assess the applicability of the standardization of the FI method, we conducted a collaborative study using FI and LO instruments in a Japanese biopharmaceutical consortium. Three types of subvisible particle preparations were shared across 12 laboratories and analyzed for their sizes and counts. The results were compared between the methods (FI and LO), inter-laboratories, and inter-instruments (Micro Flow Imaging and FlowCam). We clarified the marked difference between the detectability of FI and LO when counting highly transparent protein aggregates in the preparations. Although FlowCam provided a relatively higher number of particles compared with MFI, consistent results were obtained using the instrument from the same manufacturer in all 3 samples.